2003
DOI: 10.1542/peds.112.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Early Physical Activity Intervention Prevents Decrease of Bone Strength in Very Low Birth Weight Infants

Abstract: There is a significant postnatal decrease in the bone SOS of very low birth weight infants. A brief range-of-motion exercise attenuates the decrease in bone strength and may decrease the risk of osteopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
3
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 24 publications
7
78
3
3
Order By: Relevance
“…However, similar to our results, bone resorption markers remained constant and did not differ between intervention and CTL infants. 24,27,28 The discrepancies in bone turnover markers study between our results and those of earlier investigators may be due to inclusion of smaller, more immature infants and/or infants who were fed premature infant formula in earlier studies. Despite these subtle differences, bone biomarker results provide further evidence that physical activity promotes or maintains bone formation and mineral deposition during postnatal growth in premature VLBW infants.…”
Section: Discussioncontrasting
confidence: 82%
“…However, similar to our results, bone resorption markers remained constant and did not differ between intervention and CTL infants. 24,27,28 The discrepancies in bone turnover markers study between our results and those of earlier investigators may be due to inclusion of smaller, more immature infants and/or infants who were fed premature infant formula in earlier studies. Despite these subtle differences, bone biomarker results provide further evidence that physical activity promotes or maintains bone formation and mineral deposition during postnatal growth in premature VLBW infants.…”
Section: Discussioncontrasting
confidence: 82%
“…This is consistent with other studies that evaluated daily physical activity programs alone, without the additional periods of massage. Moyer-Mileur et al, 20,21 and others utilizing a similar protocol, 22,23 demonstrated that infants receiving 5 min of daily range-of-motion exercise had improved weight gain compared to control infants who received a 5 min daily interactive period of holding and stroking. One might argue that this 'holding and stroking' may not have the same effects as a systematic protocol of moderate pressure massage.…”
Section: Discussionmentioning
confidence: 99%
“…19 Improved bone mineralization and skeletal growth have been associated with programs of daily physical activity in preterm infants. 8,[20][21][22][23] Thus physical activity may improve weight gain through a variety of mechanisms affecting body mass of all typesFadipose, muscle and bone. Additional mechanisms have been proposed that provide a basis for the benefits of massage alone in the promotion of growth.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on tactile-kinesthetic stimulation in preterm neonates regarding growth suggest that it increases weight gain 7,19,[24][25][26] and decreases the length of hospital stay. 24,25 In our study, we did not find this difference in the daily weight gain when comparing both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention performed exclusively by the mothers was based on studies regarding the application of skin stimulations [13][14][15][16][17] and passive exercises 18,19 in preterm infants. The mothers were instructed to perform one stage at a time, and were supposed to end the sequence within 15 min, four times per day with an interval of 6 h. The tactile stimulation was performed on the cutaneous surface and the muscular area corresponding to the temporal, frontal, periorbital, nasal and perilabial regions of the face; the external side of the upper and lower limbs; and the soft parts of two or three fingers grouped were passed gently with moderate pressure, up to three times in one direction and three times in the opposite direction.…”
Section: Interventionmentioning
confidence: 99%